The Nuxalk Sputc (Eulachon)Project: Strengthening Indigenous management authority through community-driven research. (September 2020) - Beveridge, Rachelle; Moody, Megan; Murray, Grant; Darimont, Chris; Pauly, Bernie
Abstract: Indigenous peoples and their leadership remain steadfast in their commitment to manage and protect ancestral lands and waters throughout the world. In this regard, the landscape currently known as the central coast of British Columbia, Canada represents a complex and dynamic site of collaboration, negotiation, and conflict, as Indigenous leaders assert inherent rights, responsibilities, and authority to manage ancestral territories. However, while many scholars and practitioners advocate for Indigenous involvement in today's complex environmental management domain, there are few detailed examples of how Indigenous management authority is established and practiced at the community level. In this paper, we apply a decolonizing lens to examine how Indigenous authority may be advanced from the ground up. We begin with an argument for the Nuxalk Nation's jurisdiction in the management of eulachon ( Thaleichthys pacificus ), a cultural keystone species functionally extirpated throughout Nuxalk territory. We show how the community engaged Sputc Project strengthened the Nation's inherent authority to manage eulachon by articulating and representing Nuxalk knowledges, broadly engaging community, and strengthening local systems of governance. Articulating key priorities for eulachon management, we suggest that the case of eulachon presents the Canadian state with an opportunity to align with inherent Indigenous rights and responsibilities and embrace collaborative, Nation-to-Nation management approaches. As such, this case study provides a practical example to inform those working toward Indigenous resurgence and self-determination, and those who wish to understand and respect these processes.